EFFECTS OF SOWING DATE ON EMERGENCE AND YIELD OF MAIZE INBRED LINES - Tabakovic, Marijenka; Simić, Milena; Dragičević, Vesna; Oro, Violeta; Brankov, Milan; Stanisavljević, Rade (Journal on Processing and Energy in Agriculture, 2020)
The paper presents the seed production technologies of maize sown on three different sowing dates. Seeds of three maize inbred lines (L1, L2, L3) were used as a seed material in the location of Zemun Polje in 2018. The objectives of the present study was to determine the importance of different sowing dates as a method to overcome stressful conditions caused by unfavourable environmental factors, as well as to point out to a significance of the seed size in sowing. Effects of the following factors were observed in relation to the number of seeds germinated after sowing and the maize grain yield: sowing date (SD), seed fraction (LF, SF and MF) and genotype (L). The gained results indicate that the highest percentage of germinated seeds was determined in the variant L2/SD2/LF (34%), while the highest grain yield was determined in the variant L3/SD1/LF 8.86 t/ha. The standard deviation of the yield is the largest for variants with the highest yield, while the variance of seed germination is inversely proportional. The differences obtained by applying different variants in the production of the seed material point out to the significance of effects of factors and their further studying.